2012
DOI: 10.1111/j.1348-0421.2012.00430.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Malassezia microbiota in the human external auditory canal and on the sole of the foot

Abstract: Of the fungal skin microbiota, the lipophilic yeast genus Malassezia predominates at all body sites. Of the members of this genus, M. globosa, M. restricta, and M. sympodialis are the most common on the face, limbs, and trunk. In the present study, the Malassezia microbiotas in the external auditory canal and on the sole of the foot were characterized. M. slooffiae was the most common species in both the external auditory canal and on the sole of the foot, followed by M. restricta. Principal component analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…may be involved in otitis media in humans. However, a larger epidemiological study is warranted to determine the nature of this relationship (Makimura et al, 2000;Zhang et al, 2012). Findings of this study are clinically significant since these results contribute to further understand the possible effects of fungal presence on human skin.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…may be involved in otitis media in humans. However, a larger epidemiological study is warranted to determine the nature of this relationship (Makimura et al, 2000;Zhang et al, 2012). Findings of this study are clinically significant since these results contribute to further understand the possible effects of fungal presence on human skin.…”
Section: Discussionmentioning
confidence: 83%
“…The presence of M. slooffiae and M. restricta in the external auditory canal of clinically healthy people (Kaneko et al, 2010) while presence of M. sympodialis in a diabetic patient with external otitis has also been reported (Chai et al, 2000). Sugita et al (2013) reported the presence of M. globosa and M. restricta in lesions of the external auditory canal and sole of the foot (Sugita et al, 2013, Zhang et al, 2012. It is known that otitis is primarily caused by bacterial action, however, the presence of Malassezia species in infants with otitis media is yet to be reported.…”
Section: Discussionmentioning
confidence: 96%
“…All the eight swabs from these rabbits and the one from dog, used as a positive control, tested positive with PCR, giving a band at around 300 bp. The sequences obtained from all rabbits were identical to each other and showed a BLAST identity of 99.9% with uncultured Basidiomycota clone 131 (AB663497), later on named Malassezia phylotype 131, isolated from human external auditory canal, not growing on LNA medium [ 10 ]. Our specimens differed from the phylotype 131 by 2 transition G/A ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…They revealed also three new Malassezia phylopytes. Very common fungi on the soles of the exanimated foot were also Candida albicans and Cryptococcus diffluens , while, for example, Candida parapsilosis, Guehomyces pullulans, Saccharomyces cerevisiae, Rhodotorula mucilaginosa, and filamentous fungi were detected less common …”
Section: The Foot Microbiomementioning
confidence: 99%
“…The cited research had shown that the skin of the plantar heel inhabits an average of 80 species of fungus and the skin of interdigital spaces of toes on average 40‐60 species of fungi. For comparison, the torso skin is inhabited only on average by 2‐10 species of fungi . On the other hand, Oyeka and Ugwu revealed only fourteen different genera of fungi on the toe webs.…”
Section: The Foot Microbiomementioning
confidence: 99%